Computerized Evaluation of the Immunoexpression of Ki-67 Protein in Odontogenic Keratocyst and Dentigerous Cyst - Portes, Juliana (Head Neck Pathol, 2019)
Evaluation and comparison of odontogenic keratocysts and detigerous cysts immunoexpression and immunostaining intensities of Ki-67 antigen by assessing the whole extent of the epithelium (all epithelium layers in combination) and each layer individually. Ki-67 immunoexpression was evaluated in 15 odontogenic keratocysts and 6 dentigerous cysts using automated methods and the Aperio Technologies Inc. computer system. No statistically significant differences were observed in immunoexpression nor in immunostaining intensities between both lesions. Also, no statistically significant differences were found between odontogenic keratocysts from maxilla versus mandible nor primary versus recurrent. However, odontogenic keratocyst showed a significantly higher cellular proliferation index in the suprabasal layers compared to the basal layer. Assessment of the cellular proliferation index through a computerized system enabled the evaluation of all epithelial tissue without field selection. The increased Ki-67 immunoexpression in suprabasal layers of odontogenic keratocyst suggests a different biological behavior and more aggressive proliferation potential when compared to dentigerous cyst. The same result was found in recurrent odontogenic keratocysts when compared with primary ones. The odontogenic keratocysts of the maxilla and mandible have similar Ki-67 immunoexpression. The evaluation of cellular proliferation only by immunohistochemical analysis with Ki-67 antigen does not provide enough data to elucidate the biological behavior of odontogenic keratocyst.